Debt covenant slack, earnings management, and value relevance of accounting information - Dewi, Ni Putu Sintya Purnama; Wirama, Dewa Gede (International research journal of management, IT and social sciences, 2019)
This study aims to examine the effect of debt covenant slack on the value relevance of accounting information, and whether earnings management works as an intervening variable. A total of 40 non-financial companies listed in Indonesia Stock Exchange from 2013 to 2017 were selected as sample. Three hypotheses were tested using partial least square and analyzed via path analysis. This study found that debt covenant slack positively affects the value relevance of accounting information. Possibly, the tendency of small debt covenant slacks in the firms causing the information of firms’ performance to be less relevant for the investor because they believe that the firms will prioritize the debt payments rather than dividends. Furthermore, empirical evidence from this study indicates that debt covenant slack affects investors’ decision in using firms’ performance information. However, no statistically significant effect was found neither on the relationship between debt covenant slack and earnings management nor on the relationship between earnings management and the value relevance of accounting information. Hence, earnings management is not an intervening variable in the effect of debt covenant slack on the value relevance of accounting information.